Is TikTok more addictive than other social media platforms: Perception versus reality - Xie, Jianling; Gallo, Katarzyna (American Journal of Social Sciences and Humanities, 2024)
As new social media platforms emerge and the existing ones change in functionality, their impact on students may shift. The current study investigated the number of social media accounts held by college students, and examined the social media platforms students use most, time spent on social media, time spent on schoolwork, and any gender differences in these variables. Additionally, we sought to understand college students’ perceptions of the addictiveness of their major social media platform and detect possible discrepancies between their perception and reality (as measured by time spent on social media daily). A total of 306 participants were recruited from a research university in the U.S. Our results revealed that all participants had multiple active social media accounts (over 5 on average) and spent on average 3.8 hours on social media daily, while spending on average 3.7 hours on schoolwork daily. Interestingly, female participants spend more time on social media than males, as well as spent more time on schoolwork than their male counterparts, suggesting a strategy of compensation. As hypothesized, TikTok was the most popular social media platform, followed by Snapchat, Instagram, and others such as X (formerly Twitter), YouTube, and Facebook. Contrary to popular beliefs, while TikTok-favoring students were more likely to perceive that they were vulnerable to compulsive overconsumption, their time on social media per day was not significantly different from any other social media active users, F(3, 302) = 1.43, p = .23, suggesting a discrepancy between student perception and reality.